Analisis dan Evaluasi Kompetensi Profesional Guru Pkn SMP di Kepulauan Siau Kabupaten Sitaro Provinsi Sulawesi Utara - Ferry Lourens Sampel Korompis; Julien Biringan; Telly Delly Wua (CV. Kurnia Grup, 2026)
The research, including survey research, was used for descriptive purposes, and the method used was qualitative descriptive, which aimed to focus on actual problems. The collected data were initially compiled, explained, and then analyzed. Data collection was carried out through direct observation and interviews with the objects, namely teachers who teach Civics at Public Middle Schools in Siau, Sitaro Regency. Data were obtained from various sources using various data collection techniques (triangulation). The results of the study indicate that Civics teachers who teach at Public Middle Schools in Siau, Sitaro Islands Regency, are certified as professional teachers in the field of Civics teaching. There are also teachers who have not been certified working as honorary staff funded by the district government. Teachers who are not yet professional in a formal legal sense, however, carry out their duties optimally. The reality occurs if the performance of Civics teachers is not optimal due to transportation and communication constraints, the location of the school is very far from the district center, so that access to innovation in learning materials and learning media is very limited.